Your Data are (Not) My Data: The Role of Social Value Orientation in Sharing Data About Others. Issue 3 (30th June 2021) - Demmers, Joris; Weihrauch, Andrea N.; Mattison Thompson, Frauke H.
Abstract : The personal data consumers share with companies on a daily basis often also involves other people. However, prior research has focused almost exclusively on how consumers make decisions about their own data. In this research, we explore how consumers' social value orientation impacts their decisions regarding data about others. In contrast to the notion of proselfs as "selfish" decision‐makers, across four studies we find that proselfs are less likely than prosocials to share data about others with third parties. We show that this effect arises because proselfs feel less ownership over data they hold about others than prosocials, which in turn reduces their willingness to share it. Overall, this work contributes to literature on social value orientation as well as privacy decision‐making and helps marketers and policy makers in designing interdependent privacy choice contexts.